A Comparative Clinical Study of Rohitkyadi Churna and Phaltrikadi Kwatha in Kamala Roga - Yadav, Shyam Babu; Binod Kumar Singh, Binod Kumar; D.L. Bharkher (Journal of Ayurveda Campus, 2025)
Introduction: Kamala, a Pitta-predominant Vyadhi, presents clinically with yellowish discoloration of the eyes and skin, altered stool and urine color, indigestion, anorexia, fatigue, and generalized weakness. These manifestations closely resemble jaundice in modern medicine. Classical Ayurvedic formulations, Rohitkyadi Churna and Phalatrikadi Kwatha, are traditionally used to manage Kamala, but comparative clinical evidence is limited.Objectives: To evaluate and compare the efficacy of Rohitkyadi Churna and Phalatrikadi Kwath in the management of Kamala. Methods: A hospital-based, quasi-experimental clinical study was conducted at the TU Ayurveda Teaching Hospital, Kathmandu. 44 patients (aged 16–70 years) clinically diagnosed with Kamala were randomly assigned to two groups: Group A received Rohitkyadi Churna (3 g twice daily) and Group B received Phalatrikadi Kwatha (20 ml twice daily) for 45 days. Subjective parameters (Haridra Netra, Raktapitta Shakrit-Mutra, Avipaka, Hatendriya, Aruchi, Tandra, Malabaddha) and objective biochemical parameters (Serum total and direct bilirubin, SGPT, SGOT, ALP) were assessed at baseline and post-treatment. Statistical analysis was performed using paired and unpaired t-tests. Results: Both interventions produced significant improvement in clinical and biochemical parameters (p < 0.05). Group B demonstrated highly relief in Haridra Netra (91.2% ) and Avipaka (86.7% ), while Group A was more effective in normalizing Raktapitta Shakrit-Mutra (66.46% vs. 42%). Biochemically, Group A achieved higher reduction in SGPT (83.47%) and SGOT (80.49%), whereas Group B showed consistent and statistically significant improvement in liver enzymes (SGPT 47.40%, SGOT 47.02%) and greater reduction in ALP (72.54%). Both formulations were safe and well-tolerated. Conclusion : Rohitkyadi Churna and Phalatrikadi Kwatha are effective in the management of Kamala, with complementary benefits. Rohitkyadi Churna is advantageous for correcting excretory disturbances, while Phalatrikadi Kwatha offers broader hepatoprotective effects. These findings support the classical use of both formulations in evidence-based clinical practice, though larger multi centric trials with extended follow-up are warranted.